1990
DOI: 10.1128/jb.172.5.2320-2327.1990
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of regulation of the ilvGMEDA operon by using leader-attenuator-galK gene fusions

Abstract: Five of the genes for the biosynthesis of isoleucine and valine form the ilvGMEDA operon of Escherichia coli K-12. Expression of the operon responds to changes in the availability of isoleucine, leucine, and valine (ILV). Addition of an excess of all three amino acids results in reduced expression of the operon, whereas limitation for one of the three amino acids causes an increase in expression. The operon is preceded by a leader-attenuator which clearly regulates the increased expression that occurs due to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The same general conclusion comes from the more recent report of Lawther et al (33), who showed, in addition, that attenuation was dependent only on the intact leader region and not on either the ilv promoter itself or on those sequences upstream of the promoter that increased promoter strength.…”
Section: Discussionsupporting
confidence: 59%
“…The same general conclusion comes from the more recent report of Lawther et al (33), who showed, in addition, that attenuation was dependent only on the intact leader region and not on either the ilv promoter itself or on those sequences upstream of the promoter that increased promoter strength.…”
Section: Discussionsupporting
confidence: 59%
“…The ilvBN and ilvIH genes are transcribed as separate operons, whereas il-vGM is located within the ilvGMEDA operon. The il-vGMEDA and ilvBN operons are regulated by transcription attenuation, and the leader peptide reading frame of the attenuator contains regulatory codons for all three amino acids, isoleucine, leucine, and valine [9]. The leuABCD operon contains genes for the leucine biosynthesis and expression of this operon also is regulated by transcription attenuation [10].…”
Section: Introductionmentioning
confidence: 99%
“…The ilvBN and ilvIH genes are transcribed as separate operons, whereas ilvGM is located within the ilvGMEDA operon. The ilvGMEDA and ilvBN operons are regulated by transcription attenuation, and the leader peptide reading frame of the attenuator contains regulatory codons for all three amino acids, isoleucine, leucine, and valine [9]. The leuABCD operon contains genes for the leucine biosynthesis and expression of this operon also is regulated by transcription attenuation [10].…”
Section: Introductionmentioning
confidence: 99%